Evangelist Marketing of the CloverETL Software - Štýs, Miroslav (2012)
The Evangelist Marketing of the CloverETL Software diploma thesis aims at proposing a new marketing strategy for an ETL tool - CloverETL. Theoretical part comprises chapters two and three. In chapter two, the thesis attempts to cover the ETL term, which - as a separate component of the Business Intelligence architecture - is not given much space in literature. Chapter three introduces evangelist marketing, explains its origins and best practices. Practical part involves introducing the Javlin, a.s. company and its CloverETL software product. After assessing the current marketing strategy, proposal of a new strategy follows. The new strategy is built on evangelist marketing pillars. Finally, benefits of the new approach are discussed looking at stats and data - mostly Google Analytics outputs.